Characterization of plasma spray bioinert coating Al2O328wt.%MgO - Mihailo Mrdak; Časlav Lačnjevac; Marko Rakin; Darko Veljić (Zaštita Materijala)
This paper presents the results of testing mechanical and structural characteristics of plasma spray coating Al2O328wt.%MgO. Metal oxide MgO in a complex oxide Al2O328wt.%MgO modifies the properties of Al2O3 ceramics by forming spinel MgAl2O4 with excellent biomedical characteristics. The coating layers were deposited by atmospheric plasma spraying process (APS) on steel substrates of stainless steel X15Cr13 (EN 1.4024). The aim of this study was to examine the effect of the strength of the plasma current (700A, 800A and 900A) on the mechanical properties of the Al2O3MgO coating, pore content and microstructure of the layers. Testing microhardness of the layers using the HV0.3 method, the bond strength using the tensile method and microstructure using optical microscopy (OM) and scanning electron microscopy (SEM) have confirmed that, by controlling the plasma current, layers of the coating system Al2O328wt.%MgO can be deposited with good mechanical and microstructural characteristics suitable for use in manufacture of implants.